The Assessment of Indonesian Students’ Creative Writing in Recount Texts: A Transitivity Analysis - Anugrah, Yasmin Kamila Eka; Safriyani, Rizka; Khoiril (ICONELT, 2024)
This research aims to examine the standard transitivity processes used by eighth-grade students in their recount texts and identify the most dominant types of processes. The Merdeka Curriculum for junior high school emphasizes developing students’ writing skills, particularly in recounting personal experiences. Using a qualitative approach with a case study design and content analysis method, this research analyzes 24 recount texts written by eighth-grade students in class D at a state junior high school in Surabaya, Indonesia. The transitivity framework of Halliday and Matthiessen (2004) is applied to categorize processes in these texts. The results show that all six transitivity processes were found in students’ recount texts, but students commonly mentioned three transitivity processes: Material, Mental, and Relational. Students primarily use material processes (47%), followed by mental processes (25%), relational (15%), existential (9%), behavioral (3%), and verbal (1%). The high frequency of material processing indicates that students are proficient in describing physical actions and events. However, in terms of creative writing, students exhibit limitations in expressing the existence of objects (existential), human behavioral responses (behavioral), and the process of saying something (verbal). Challenges such as grammatical errors and lack of vocabulary highlight the need for targeted instruction in grammatical structure and vocabulary expansion. The researcher suggests that activities such as rearranging jumbled words and word games could enhance students’ grasp of grammar and vocabulary to improve their ability to write engaging personal experience texts.